JOB STRESS AND PERFORMANCE OF BANKERS IN LAGOS, NIGERIA - Akindoyin, Ebenezer Olufemi; Oladiji, Tolulope Olufunmilayo (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
Employees are the most valuable asset of any organisation as they may profoundly affect the company’s reputation and influence productivity and profitability. Employees often assume the principal responsibility for the majority of critical tasks, customer happiness, and the quality of products and events. The study investigated job stress and performance of bankers in Lagos, Nigeria. The paper was anchored onto goal-setting theory, using accidental sampling technique with the use of questionnaire to get information from 255 participants. Hypotheses were tested using inferential statistics. Findings indicated that stress influences employee performance R2= .453 value indicate that job stress accounts for 45.3% of the variance of employee’s performance among the commercial banks staff in Lagos State. At F(1,253)= 209.208, p= .000, which is less than .05. Gender had no significant influence on employee’s performance of the participants at t= 259, df= 253 and p=.796. Lastly, the interaction of job stress and gender also had no significant influence on the employees’ performance. Consequently, it is advisable for commercial banks in Lagos to employ additional capable workers to alleviate the stress encountered by bankers. Gender diversity also ought to be promoted within the banking sector.